2021
DOI: 10.1371/journal.pone.0243858
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alginate microencapsulation improves the short-term oral bioavailability of cannabidiol when administered with deoxycholic acid

Abstract: Background Cannabidiol (CBD) confers therapeutic effects in some neurological disorders via modulation of inflammatory, oxidative and cell-signalling pathways. However, CBD is lipophilic and highly photooxidative with low oral bioavailability in plasma and brain. In this study, we aimed to design and test a CBD microencapsulation method as a drug delivery strategy to improve the absorption of CBD. Additionally, we evaluated the brain uptake of CBD capsules when administered alongside capsules containing a perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In mice, 20 studies reported anxiety outcomes (Aso et al, 2019; Assareh et al, 2020; Breuer et al, 2016; Casarotto et al, 2010; Deiana et al, 2012; Florensa-Zanuy et al, 2021; Kasten et al, 2019; Long et al, 2010, 2012; Myers et al, 2019; Nardo et al, 2014; Navarrete et al, 2018; Onaivi et al, 1990; Schiavon et al, 2016; Todd and Arnold, 2016; Todd et al, 2017; Twardowschy et al, 2013; Uribe-Mariño et al, 2012; Zagzoog et al, 2020; Zieba et al, 2019) and four studies reported PK outcomes but no anxiety outcomes, or no CBD-vehicle comparison was reported (Anderson et al, 2021; Brzozowska et al, 2016; Majimbi et al, 2021; Pang et al, 2021). In two studies, both types of outcomes were reported (Deiana et al, 2012; Zieba et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, 20 studies reported anxiety outcomes (Aso et al, 2019; Assareh et al, 2020; Breuer et al, 2016; Casarotto et al, 2010; Deiana et al, 2012; Florensa-Zanuy et al, 2021; Kasten et al, 2019; Long et al, 2010, 2012; Myers et al, 2019; Nardo et al, 2014; Navarrete et al, 2018; Onaivi et al, 1990; Schiavon et al, 2016; Todd and Arnold, 2016; Todd et al, 2017; Twardowschy et al, 2013; Uribe-Mariño et al, 2012; Zagzoog et al, 2020; Zieba et al, 2019) and four studies reported PK outcomes but no anxiety outcomes, or no CBD-vehicle comparison was reported (Anderson et al, 2021; Brzozowska et al, 2016; Majimbi et al, 2021; Pang et al, 2021). In two studies, both types of outcomes were reported (Deiana et al, 2012; Zieba et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated for rats (Cherniakov et al, 2017: 27) and humans (Taylor et al, 2018: 1061), but to a lesser extent for mice; Pang et al (2021: 2044) reported no differences in T max between six mice. In addition, T max strongly depends on the formulation used in rats (Cherniakov et al, 2017: 27), mice (Majimbi et al, 2021: 8) and humans (Izgelov, Davidson et al, 2020a: 3). Thus, in some cases, the anxiety test may have already been terminated at the time plasma levels of CBD have reached their peak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[101] Bile acids are widely used to improve drug delivery, including by improving transport across membranes, improving capsule strength and increasing drug release. [102][103][104][105][106] For example, deoxycholic acid, a secondary bile acid, has been shown to improve transport across the blood-brain barrier. [107] This may be useful in transportation across the blood labyrinthine barrier that connects the inner ear to the vasculature; to date however, this has not been established in the literature.…”
Section: Bile Acidsmentioning
confidence: 99%
“…Naturally occurring secondary bile acid, namely deoxycholic acid (DCA), was found to exert positive and stabilising effects on nanogel capsules for oral delivery of a hydrophobic drug [ 24 ]. Majimbi et al observed greater bioavailability of cannabinol when administered in the form of DCA-enhanced microcapsules [ 25 ]. Li et al designed DCA-based micelles for targeted drug delivery of an antitumor agent [ 26 ].…”
Section: Introductionmentioning
confidence: 99%